Illya Beads Store / Illya Maisarah Mohd Nor Hakim - Illya Maisarah, Mohd Nor Hakim (2020)
Our shop concept is to provided quality item in fashion industry .Illya beads are provided basic tailoring tools and beads. We are selling the most tools needed by the customer. So we just provided the basic things only. Such as fabric scissors, tailor’s chalk, measuring tape, ruler, hand sewing needles, machine sewing needles , thread, pins , tracing wheel , tracing paper and seam ripper.We are more focused on selling beads, because in seri Iskandar they didn’t have a store that focused on selling beads. So we were the first store that focused on selling beads. Our store are provided a beautiful variety beads, so they have many options when they come to our place. For example, seed beads, natural morganite beads, agate stone beads and many more. It is made up of various colours, shapes and sizes. Our target market is fashion student and lecturer at UiTM Seri Iskandar . Fashion student are needs the goods in our store compared to other customers. Before our store are open, they would often go to KL and return to Perak at the same day . Our store make it easy for them to find quality goods like in Kuala Lumpur . So they didn’t have to go to Kuala Lumpur just for that goods.We focus on fashion student it is because our store are selling sewing tools and beads. To make it more attractive and interesting , we decide to make some innovation by implaying our creativity and modern element in this decoration and packaging .We have done some research and we try to provide a quality product to attrac customer . Normally , student will by their assignment staff during the hactic week and final week . So we will prepared a enough product for them . Based on the objective above , we are venturing into fashion industry . Illya beads has the potential of being a profitable business if it is done in modern way with large scale and systematically manageed. Me and my partner will also can get profitability from that . We eill expect that our business will become more developed in the near future because with the new idea , the demand will increadse not only during any occasion. This will give more advantages for us to make our product more profitable and stable in the long run